Isotretinoína oral em dose baixa versus tretinoína tópica na prevenção de queratoses actínicas em pacientes imunocompetentes: estudo clínico randomizado e comparativo - Ianhez, Mayra [UNIFESP] (2016)
Introduction: Chronic photoexposure can generate actinic keratosis and damage to the surrounding normal skin (field cancerization), which can evolve to skin cancer. Currently, the treatment of actinic keratosis addresses not only the destruction of individual lesions (using methods such as liquid nitrogen cryosurgery, electrocoagulation, trichloroacetic acid, and shaving), but also the treatment of field cancerization (using drugs such as 5-fluorouracil, imiquimod, ingenol mebutate, oral and topical retinoids, chemical peelings, and photodynamic therapy). Most studies involving retinoids have as purpose and primary outcome the prevention of nonmelanoma skin cancer. Therefore, few data are available about their use for the treatment of actinic keratosis. Oral and topical retinoids can be used for prevention and treatment of multiple actinic keratoses and field cancerization, especially in association with sunscreen and liquid nitrogen cryosurgery. Objectives: The primary objective of this research was to evaluate the clinical, histopathological, and immunohistochemical effects on the epidermis and dermis of the studied drugs for the treatment of multiple actinic keratoses of the face and forearms in immunocompetent patients. The secondary objectives were: 1) to evaluate the tolerability and safety of the medications; 2) to demonstrate the impact of the treatments on quality of life; 3) to investigate the reproducibility of lesion count as a parameter of efficacy; 4) to verify the role of cryosurgey associated to daily use of sunscreen in the control of actinic keratosis. Methods: This is an open, randomized, propective, and comparative clinical trial, including 61 participants, from 50 to 75 years of age, from both genders, with 5 to 60 visible and/or palpable actinic keratoses on the face and forearms. At the beginning (T0) and after 120 days (T120), all participants underwent liquid nitrogen cryosurgery to treat their actinic keratoses. Posteriorly, they were randomized in two treatment groups: 30 took oral isotretinoin, at the dose of 10 mg/day (ISO group), and 31 used 0.05% topical tretinoin cream every other night (TRE group), for 6 months (T300). All the subjects used SPF 60 sunscreen during the whole study period. At the beginning of the randomization (T120) and at the end of the study (T300), two biopsies were performed in the left forearm. The efficacy was evaluated using clinical (number of actinic keratoses) and histopathological parameters (hematoxilin-eosin and Weigert-Van Gieson staining, the latter for elastic fibers), as well as immunohistochemical markers of carcinogenesis (proteins p53, Bcl-2, and Bax) before and after the treatments. The safety evaluation included the report and observation of side effects and biochemical laboratory tests for the participants of the ISO group. Results: A decrease in the number of actinic keratoses related to liquid nitrogen cryosurgery and the use of SPF 60 sunscreen was observed between T0 and T120 (-39%) and to the treatments for field cancerization with oral isotretinoin (-33%) and topical tretinoin (-23%), cryosurgery and SPF 60 sunscreen between T120 and T300. The histopathological and immunohistochemical findings demonstrated: thinning of the stratum corneum and reduction of p53 and Bax expression between T120 and T300. Thickening of the basal to the granular layer and increased expression of Bcl-2 protein were observed in both groups. No modifications were found in the elastic tissue. In general, the treatment groups did not differ (p > 0.1). Only slight side effects were observed in both groups, except severe xerophthalmia in one patient of the ISO group. Between T120 and T180, the levels of total cholesterol and triglycerides increased in 76% and 61% of the participants, respectively, and this increase was around 30% of the initial value, returning to normal in T300 without the need to change or interrupt the treatment. Conclusion: Both low-dose oral isotretinoin and 0.05% topical tretinoin cream improved clinical, histopathological, and immunohistochemical parameters in patients with multiple actinic keratoses and field cancerization, without differences between them. The therapeutic choice of retinoids for field cancerization should take into consideration the patient?s profile, particularly in relation to the risk of side effects.